The basis for Chinese agricultural growth in the 1980s and 1990s: a comment on Document no. 1, 1984. - Stone, Bruce (Cambridge University Press, 1985)
Rather than considering the possible ramifications of each clause of Document No. 1, 1984 separately, this comment will focus on aspects of the document which are consistent with Chinese development strategy in the 1980s and those which acknowledge the principal vulnerabilities of the strategy as they pertain to agriculture. Much of the document is concerned with: (1) consolidating the gains achieved since the late 1970s in transforming rural organization via the production responsibility system and the attendant liberalization of rural markets; (2) extending the current areas of profitability in terms of increased production and the sale of farm goods that have become available through this transformation and especially in terms of reaping the rewards from specialization, hitherto untapped; and (3) more effectively setting the stage for future growth by attempting to generate confidence as to the durability of these organizational, and other critical policy changes.